Identifying Political Risk Management Strategies in International Construction Projects - Tengyuan Chang; Bon-Gang Hwang; Xiaopeng Deng; Xianbo Zhao (Advances in Civil Engineering)
International construction projects are plagued with political risk, and international construction enterprises (ICEs) must manage this risk to survive. However, little attention has been devoted to political risk management strategies in international construction projects. To fill this research gap, a total of 27 possible strategies were identified through a comprehensive literature review and validated by a pilot survey with 10 international experts. Appraisals of these 27 strategies by relevant professionals were collected using questionnaires, 155 of which were returned. Exploratory factor analysis was conducted to explore the interrelationships among these 27 strategies. The results show that all of the 27 strategies are important for political risk management in international construction projects. Moreover, these 27 strategies were clustered into six components, namely, (1) making correct decisions, (2) conducting favorable negotiations, (3) completing full preparations, (4) shaping a good environment, (5) reducing unnecessary mistakes, and (6) obtaining a reasonable response. The 6 components can be regarded as 6 typical management techniques that contribute to political risk management in the preproject phase, project implementation phase, and postevent phases. The findings may help practitioners gain an in-depth understanding of political risk management strategies in international construction projects and provide a useful reference for ICEs to manage political risks when venturing outside their home countries.